A Brief Study of Materials and Sounds of Bonang Instrument from Selected Region - Hasnizam, Abdul Wahid; Sinin, Hamdan; Iran Amri, Musoddiq (Asian Economic and Social Society (AESS), 2018)
Gamelan is a melodic instrument typically made from bronze and placed on a resonator. Initial observation proved that there are no two gamelan tuned exactly alike as mentioned earlier by Rossing (2000). The tuning methods during the crafting process were made in the fieldwork. In our initial observation, it is concluded that there is no specific reference to any specific tune devices as had been practiced on crafting western musical instruments. Gamelan are known and recognized to have a specific scaled that is either in the five tones Slendro or seven tones Pelog scales. Interestingly, in Malaysian practice the ensemble are typically tune diatonically to pentatonic scale, which provoked interesting discussion by Dufford (2014).Preliminary findings on the Gamelan instruments have highlighted some issues, particularly on its physical composition, tunings, as well as the sound it produces. This paper will discuss some of the preliminary findings and issues related to the investigation on acoustic properties of selected Gamelan instruments.